Keamanan Jaringan komputer Dalam Bisnis E-Commerce (Studi Kasus: Kebocoran Data Tokopedia 2020) - Dhifa Dharma Rafadhani; Dinda Pratiwi; Nabila Sayidina (Journal of Information Systems and Business Technology, 2025)
The rapid development of digital activities in the modern era demands a way for humans to carry out various digital activities. Under these conditions, cloud computing has emerged as a paradigmatic solution that supports digital transformation by providing data storage services, application processing, and online collaboration. This study is to analyze the use of cloud computing in supporting various dimensions of digital activities and identify its strategic benefits and challenges. In addition, this digital technology is equipped with advanced security, multi-factor authentication, and role-based access management that can minimize data security risks. This study applies a systematic literature review with a qualitative approach that focuses on scientific publications and the latest industry reports (2019–2024). This study shows that cloud computing significantly supports digital activities through increased infrastructure scalability, accessibility of services from anywhere, efficiency of operational costs based on pay-per-use, and acceleration of innovation with ready-to-use services (such as AI and Big Data). However, challenges remain in the aspects of cybersecurity, the complexity of multi-cloud management, and dependence on service providers. This study confirms that cloud computing not only functions as a technology enabler, but also as a strategic pillar in building digital competitiveness in the modern era. The implications suggest that organizations need to formulate a robust cloud strategy, strengthen governance, and address security challenges to maximize its value and benefits.